Effect of Auricular Acupressure on Acute Pain in Nursing Home Residents with Mild Dementia: A Single-Blind, Randomized, Sham-Controlled Study. (10th March 2022) - Zhang, Jun-Jun; Yu, Li; Mei, Jun-Hui; Wang, Hong-Xin; Gao, Hai-Xiang; Fu, Ju-Fang; Cheng, Ye; Gao, Lu-Lu; Bu, Lei; Yu, Jian-Qiang; Wang, Carol Chunfeng; Li, Yu-Xiang
Abstract : Introduction . Acute pain is a prevalent problem for dementia residents in nursing homes. A variety of intervention strategies have been applied to address this problem. However, there remains an issue of inadequate pain control. This study aims to explore the analgesic efficacy of auricular acupressure (AA) for dementia residents with acute pain in nursing homes. Methods . A multicenter, single-blind, randomized, and sham-controlled clinical trial was performed in three nursing homes in Yinchuan, China. All of the 206 eligible patients with acute pain were randomly divided into two groups for real AA therapy or sham AA (at sham point stimulation) therapy. The primary outcome was measured with a face pain scale revised (FPS-R) score before the procedure, 5 min after the start of the intervention, and 5 min after finishing the procedure. Secondary outcomes covered three physiological parameters, adverse reactions observed, satisfaction level of caregivers, acceptance of patients, and additional use of analgesics. Results . There was a significant difference in pain scores based on FPS-R between the two groups (p < 0.01 ). Pain score in the true AA group was 1.84 ± 0.23, compared with 2.22 ± 0.81 in the sham AA group. No adverse events were found during the whole procedure for all patients. The satisfaction level of caregivers and acceptance of patients in the real AA group were significantly higher than those in the sham AA group. Conclusion . This study shows that real AA was an alternative analgesic modality in reducing acute pain in patients with mild dementia.